Undang-undang keluarga dan prosedur - Mohd Zin, Najibah (Department of Islamic Law & Harun M. Hashim Law Centre, 2009)
This book discusses contemporary issues in Syariah courts that relate to family law and procedure. Family law issues include runaway bride, welfare of illegitimate child, custody of infant, and maintenance of child. Procedural issues include ex-parte application, trial in the absence of defendant, application for injunction, and settlement of marital disputes by sulh.